2021
DOI: 10.1155/2021/5541255
|View full text |Cite
|
Sign up to set email alerts
|

Human Gait Analysis and Prediction Using the Levenberg-Marquardt Method

Abstract: A high-accuracy gait data prediction model can be used to design prosthesis and orthosis for people having amputations or ailments of the lower limb. The objective of this study is to observe the gait data of different subjects and design a neural network to predict future gait angles for fixed speeds. The data were recorded via a Biometrics goniometer, while the subjects were walking on a treadmill for 20 seconds each at 2.4 kmph, 3.6 kmph, and 5.4 kmph. The data were then imported into Matlab, filtered to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…ese real-time samples are extracted through the Levenberg-Marquardt method, and their artifacts are removed using the Butterworth filters in order to train the neural network effectively. e gait data are observed from 5-subjects at distinct speeds 2.4, 3.2, and 5.4 kmph and in total 45 instances are utilized for evaluation [27]. ough the proposed NN achieved better accuracy for tested data, it is not suitable for dynamic movements, and the tested data range are very low.…”
Section: Related Workmentioning
confidence: 99%
“…ese real-time samples are extracted through the Levenberg-Marquardt method, and their artifacts are removed using the Butterworth filters in order to train the neural network effectively. e gait data are observed from 5-subjects at distinct speeds 2.4, 3.2, and 5.4 kmph and in total 45 instances are utilized for evaluation [27]. ough the proposed NN achieved better accuracy for tested data, it is not suitable for dynamic movements, and the tested data range are very low.…”
Section: Related Workmentioning
confidence: 99%
“…Levenberg-Marquardt backpropagation was chosen as the training algorithm due to its better performance than another training algorithm [12]. Some studies found that Levenberg-Marquardt backpropagation has classification results above 95% [27]- [30]. EMG signals were classified into 8 classes, i.e., treadmill walking with speed 1, labeled as T1, treadmill walking with speed 2, labeled as T2, treadmill walking with speed 3, labeled as T3, treadmill walking with speed 4, labeled as T4, treadmill walking with speed 5 labeled as T5, ground walking labeled as GW, walked upstairs Labelled as UW and walked down stair labeled as DW.…”
Section: Classification Methodsmentioning
confidence: 99%
“…This framework achieved better performance in terms of performance. However, this architecture has a drawback in that it is inappropriate for dynamic walk patterns [13].…”
Section: Related Workmentioning
confidence: 99%